Debranning of purple wheat: recovery of anthocyanin-rich fractions and their use in pasta production. (January 2017) - Zanoletti, Miriam; Abbasi Parizad, Parisa; Lavelli, Vera; Cecchini, Cristina; Menesatti, Paolo; Marti, Alessandra; Pagani, M. Ambrogina
Abstract: Debranning is a pre-milling treatment that partially removes the external coats and the aleurone layer of the kernel, allowing the selective recovery of bioactive compounds, such as fiber and phenolic compounds. A two-step debranning process was applied to purple wheat, a naturally antioxidant-rich variety, that removed 9.7% of the material. Debranned fractions from the first (F1; 3.7% of the whole grain) and the second (F2; 6.0% of the debranned grain after the first step) step were used separately to produce fiber-enriched pasta. Bran from conventional milling (CB) was also used as a control. F1 and F2 had a higher or comparable content in total and soluble fiber than CB. Moreover, both samples exhibited a higher ferric reducing-antioxidant power (FRAP) than CB, whereas the highest amount of anthocyanins was found in F1 (695 ± 64 μg/g). When compared with CB-enriched pasta, samples enriched with either F1 or F2 had similar FRAP values (2.6 ± 0.1 and 2.3 ± 0.2 μmol Fe(II)/g for pasta with F1 and F2, respectively), and a higher amount of anthocyanins (67.9 ± 0.9 and 60 ± 1 μg/g for pasta with F1 and F2, respectively), while retaining a fair cooking quality. Highlights: Purple wheat is a naturally antioxidant-rich variety. Fractions from debranning were rich in fibre and anthocyans. Pasta with debranning fractions contains more anthocyans than bran-enriched pasta. Debranning of purple wheat is an interesting tool for pasta production.